2019
DOI: 10.5194/bg-2019-342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the contributions of riverine vs. oceanic nitrogen to hypoxia in the East China Sea

Abstract: In the East China Sea, hypoxia (oxygen ≤ 62.5 mmol m −3 ) is frequently observed off the Changjiang (or Yangtze) River estuary covering up to about 15,000 km 2 . The Changjiang River is a major contributor to hypoxia formation because it discharges large amounts of freshwater and nutrients into the region. However, modelling and observational studies have suggested that intrusions of nutrient-rich oceanic water from the Kuroshio Current also contribute to hypoxia formation. The relative contributions of riveri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Higher wind speed causes stronger vertical mixing and vanishing of hypoxia (Zheng et al, 2016). In July 2015, 1.5 months before our survey, hypoxia was terminated by a typhoon, but 2 d later, hypoxic conditions were reestablished (Guo et al, 2019). Our field measurements showed that the upper boundary of the DO depletion is strongly linked to the upper boundary of KSSW (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Higher wind speed causes stronger vertical mixing and vanishing of hypoxia (Zheng et al, 2016). In July 2015, 1.5 months before our survey, hypoxia was terminated by a typhoon, but 2 d later, hypoxic conditions were reestablished (Guo et al, 2019). Our field measurements showed that the upper boundary of the DO depletion is strongly linked to the upper boundary of KSSW (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Intensive hypoxia can start from very shallow depths (at 4-8 m) in the northern area (Fig. 5g), and it can develop very fast under favorable conditions (Guo et al, 2019). At the same time, the bottom layer there can be easily ventilated by wind stirring or downwelling as we observed at section N15 in 2015 (Fig.…”
Section: Discussionmentioning
confidence: 71%